2016
DOI: 10.1016/j.lwt.2015.09.046
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the efficacy of different yeast strains for alcohol level reduction in wine by respiration

Abstract: a b s t r a c tWe have recently shown that ethanol yields in winemaking can be reduced by taking advantage of the respiratory metabolism of some non-Saccharomyces yeast species. Using an orthogonal design we have now addressed the impact of three environmental factors (temperature, nitrogen source, and oxygen supply level) on the aerobic metabolism in synthetic must of Saccharomyces cerevisiae, Metschnikowia pulcherrima, Kluyveromyces lactis, and Candida sake. An integrative parameter, Efficacy (efficacy for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 22 publications
3
38
0
Order By: Relevance
“…The interesting aspect is the higher yield with the addition of nutrients. The same behavior has been described by other authors for T. delbrueckii [41] and other non-Saccharomyces yeast species [42], suggesting a role of nitrogen in the promotion of a higher rate of fermentation over other metabolic functions.…”
Section: Fermentation Parameterssupporting
confidence: 87%
“…The interesting aspect is the higher yield with the addition of nutrients. The same behavior has been described by other authors for T. delbrueckii [41] and other non-Saccharomyces yeast species [42], suggesting a role of nitrogen in the promotion of a higher rate of fermentation over other metabolic functions.…”
Section: Fermentation Parameterssupporting
confidence: 87%
“…Respiratory consumption of sugars [52][53][54][55] Saccharomyces cerevisiae Genetic engineering [56][57][58] S. cerevisiae is efficient at converting sugar to alcohol and has a preeminent tolerance to the stressful conditions encountered during alcoholic fermentation. Thus, one of the methods explored consists in breeding different S. cerevisiae strains to select less ethanol producer yeast [43,44].…”
Section: Saccharomyces Kudriavzeviimentioning
confidence: 99%
“…This appears to be the case where the volatile production (except ethanol) was significantly lower in the high sugar fermentation especially for esters (Table S1). It has been suggested that oxygenation and the addition of assimilable nitrogen can be used to reduce the toxic effects of ethanol on yeasts (Rodrigues et al, 2016).…”
Section: Effects Of Sugar Concentration On Volatile Productionmentioning
confidence: 99%